Balancing Carrier Dynamics in Oxygen‐Vacancy‐Tuned Amorphous Ga2O3 Thin‐Film Self‐Powered Photoelectrochemical‐Type Solar‐Blind Photodetector Arrays for Underwater Imaging - Ke Ding; Hong Zhang; Jili Jiang; Jiangshuai Luo; Rouling Wu; Lijuan Ye; Yan Tang; Di Pang; Honglin Li; Wanjun Li (Advanced Science)
Abstract Underwater imaging technology plays a pivotal role in marine exploration and reconnaissance, necessitating photodetectors (PDs) with high responsivity, fast response speed, and low preparation costs. This study presents the synergistic optimization of responsivity and response speed in self‐powered photoelectrochemical (PEC)‐type photodetector arrays based on oxygen‐vacancy‐tuned amorphous gallium oxide (a‐Ga2O3) thin films, specifically designed for solar‐blind underwater detection. Utilizing a low‐cost one‐step sputtering process with controlled oxygen flow, a‐Ga2O3 thin films with varying oxygen vacancy (VO) concentrations are fabricated. By balancing the trade‐offs among electrocatalytic reactions, charge transfer, carrier recombination, and trapping, both the responsivity and response speed of a‐Ga2O3‐based self‐powered PEC‐PDs are simultaneously improved. Consequently, the optimized PEC‐PDs demonstrated exceptional performance, achieving a responsivity of 33.75 mA W−1 and response times of 12.8 ms (rise) and 31.3 ms (decay), outperforming the vast majority of similar devices. Furthermore, a pronounced positive correlation between anomalous transient photocurrent spikes and the concentration of VO defects is observed, offering compelling evidence for VO‐mediated indirect recombination. Finally, the proof‐of‐concept solar‐blind underwater imaging system, utilizing an array of self‐powered PEC‐PDs, demonstrated clear imaging capabilities in seawater. This work provides valuable insight into the potential for developing cost‐effective, high‐performance a‐Ga2O3 thin‐film‐based PEC‐PDs for advanced underwater imaging technology.